SECOND RECORD OF THE ASIAN SPECIES SCOLYTOPLATYPUS TYCON BLANDFORD, 1893 (CURCULIONIDAE: SCOLYTINAE) FOR THE NORTH CAUCASUS (Acta Entomologica Serbica, 2023)
Species of the genus Scolytoplatypus C. F. C. Schaufuss, 1891 are distributed in the Afrotropical and Oriental regions. However, cases of species invasion into other areas are common. After fourteen years on the territory of North Caucasus (Russia: Republic of Adygea), one far-eastern species, Scolytoplatypus tycon Blandford, 1893 (Curculionidae: Scolytinae), was recorded for a second time.